2018
DOI: 10.1186/s12944-018-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid compositional changes and oxidation status of ultra-high temperature treated Milk

Abstract: BackgroundMilk fat is one of the complex fat and most sensitive biochemical compounds towards auto-oxidation. To enhance the shelf life, milk is subjected to Ultra-high Temperature (UHT) treatment followed by aseptic packaging. During the storage, several chemical and biochemical changes take place in lipid fraction of UHT milk. In current investigation, the effect of UHT treatment and storage was determined by making a comparison in fatty acid profile, triglyceride composition, organic acids and lipid oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…e results show that the human milk powder with pasteurization treatment (HMP) has a shorter shelf life since, as can be seen in Figure 4, this milk showed the highest percentage of fat oxidation (lipolysis). ese results are in agreement with the report made by Ajmal et al [25], reporting that ultrahigh temperatures treatment induced significant changes in the triglyceride profile of milk cleaving the bond between the fatty acids and glycerol leading to the formation of free fatty acids and later oxidation.…”
Section: Prediction Of the Shelf Life Of Human Milk Powder Through Thsupporting
confidence: 93%
“…e results show that the human milk powder with pasteurization treatment (HMP) has a shorter shelf life since, as can be seen in Figure 4, this milk showed the highest percentage of fat oxidation (lipolysis). ese results are in agreement with the report made by Ajmal et al [25], reporting that ultrahigh temperatures treatment induced significant changes in the triglyceride profile of milk cleaving the bond between the fatty acids and glycerol leading to the formation of free fatty acids and later oxidation.…”
Section: Prediction Of the Shelf Life Of Human Milk Powder Through Thsupporting
confidence: 93%
“…Use of induction period for the measurement of oxidative stability of milk is studied in a limited way. Ajmal et al [60] studied the induction period of UHT treated milk stored for 90 days, it was found that induction period decreased with the progression of storage length. For the determination of oxidative stability of low melting point fractions of buffalo butter oil, induction period was used as a key parameter [40].…”
Section: Discussionmentioning
confidence: 99%
“…UHT is used in the dairy industry as a means of preparing milk for long-term storage without the need for refrigeration. Ajmal et al [50] found that the level of short-, medium-, and long-chain FA decreased in UHT milk compared to raw milk, and the FA profile of UHT milk remained stable during 30 days of storage. However, studies have reported Maillard reaction products present in milk post UHT processing [51], and "sulphury flavours" in milk have also been reported as a result of UHT processing [52].…”
Section: Range Of Lipid Oxidation In Six Retail Infant Milk Formula Pmentioning
confidence: 99%